Estudo de titanatos nanoestruturados obtidos por tratamento hidrotérmico de óxido de titânio em meio alcalino - Morgado Júnior, Edisson (2007)
TiTanate NanoTubes (TTNT) were synthesized by hydrothermal alkali treatment of TiO2 anatase followed by repeated washings with distinct degrees of proton exchange. TTNT samples with different sodium contents were characterized, as synthesized and after heattreatment (200-800ºC), by X-ray diffraction, scanning and transmission electron microscopy, electron diffraction, thermal analysis, nitrogen adsorption and spectroscopic techniques like FTIR and UV-Vis diffuse reflectance. It was demonstrated that TTNTs consist of trititanate structure with general formula NaxH2−xTi3O7·nH2O, retaining interlayer water in its multiwalled structure. The removal of sodium reduces the amount of water and contracts the interlayer space leading, combined with other factors, to increased specific surface area and mesopore volume. TTNTs are mesoporous materials with two main contributions: pores smaller than 10 nm due to the inner volume of nanotubes and larger pores within 5-60 nm attributed to the interparticles space. Chemical composition and crystal structure of TTNTs do not depend on the average crystal size of the precursor TiO2-anatase, but this parameter affects significantly the morphology and textural properties of the nanostructured product. Such dependence has been rationalized using a dissolution-recrystallization mechanism, which takes into account the dissolution rate of the starting anatase and its influence on the relative rates of growth and curving of intermediate nanosheets. The thermal stability of TTNT is defined by the sodium content and in a lower extent by the crystallinity of the starting anatase. It has been demonstrated that after losing interlayer water within the range 100-200ºC, TTNT transforms, at least partially, into an intermediate hexatitanate NaxH2−xTi6O13 still retaining the nanotubular morphology. Further thermal transformation of the nanostructured tri- and hexatitanates occurs at higher or lower temperature and follows different routes depending on the sodium content in the structure. At high sodium load (water washed samples) they sinter and grow towards bigger crystals of Na2Ti3O7 and Na2Ti6O13 in the form of rods and ribbons. In contrast, protonated TTNTs evolve to nanotubes of TiO2(B), which easily convert to anatase nanorods above 400ºC. Besides hydroxyls and Lewis acidity typical of titanium oxides, TTNTs show a small contribution of protonic acidity capable of coordinating with pyridine at 150ºC, which is lost after calcination and conversion into anatase. The isoeletric point of TTNTs was measured within the range 2.5-4.0, indicating behavior of a weak acid. Despite displaying semiconductor characteristics exhibiting typical absorption in the UV-Vis spectrum with estimated bandgap energy slightly higher than that of its TiO2 precursor, TTNTs showed very low performance in the photocatalytic degradation of cationic and anionic dyes. It was concluded that the basic reason resides in its layered titanate structure, which in comparison with the TiO2 form would be more prone to the so undesired electron-hole pair recombination, thus inhibiting the photooxidation reactions. After calcination of the protonated TTNT into anatase nanorods, the photocatalytic activity improved but not to the same level as that exhibited by its precursor anatase